Can We Avoid Implant-selection Errors in Total Joint Arthroplasty?. Issue 1 (January 2019) - Ast, Michael P.; Mayman, David J.; Bostrom, Mathias P.; Gonzalez Della Valle, Alejandro; Haas, Steven B.
Abstract: Background: Implant selection in the operating room is a manual process. This manual process combined with complex compatibility rules and inconsistent implant labeling may lead to implant-selection errors. These might be reduced using an automated process; however, little is known about the efficacy of available automated error-reduction systems in the operating room. Questions/purposes: (1) How often do implant-selection errors occur at a high-volume institution? (2) What types of implant-selection errors are most common? Methods: We retrospectively evaluated our implant log database of 22, 847 primary THAs and TKAs to identify selection errors. There were 10, 689 THAs and 12, 167 TKAs included during the study period from 2012 to 2017; there were no exclusions and we had no missing data in this study. The system provided an output of errors identified, and these errors were then manually confirmed by reviewing implant logs for each case found in the medical records. Only those errors that were identified by the system were manually confirmed. During this time period all errors for all procedures were captured and presented as a proportion. Errors identified by the software were manually confirmed. We then categorized each mismatch to further delineate the nature of these events. Results: One hundred sixty-nine errors were identified by the software system just before implantation, representing 0.74 of the 22, 847 procedures performed. In 15 procedures, the wrong side was selected. Twenty-five procedures had a femoral head selected that did not match the acetabular liner. In one procedure, the femoral head taper differed from the femoral stem taper. There were 46 procedures in which there was a size mismatch between the acetabular shell and the liner. The most common error in TKA that occurred in 46 procedures was a mismatch between the tibia polyethylene insert and the tibial tray. There were 13 procedures in which the tibial insert was not matched to the femoral component according to the manufacturer's guidelines. Selection errors were identified before implantation in all procedures. Conclusions: Despite an automated verification process, 0.74% of the arthroplasties performed had an implant-selection error that was identified by the software verification. The prevalence of incorrect/mismatched hip and knee prostheses is unknown but almost certainly underreported. Future studies should investigate the prevalence of these errors in a multicenter evaluation with varying volumes across the involved sites. Based on our results, institutions and management should consider an automated verification process rather than a manual process to help decrease implant-selection errors in the operating room. Level of Evidence: Level IV, therapeutic study.